2016
DOI: 10.3892/ijmm.2016.2834
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective effects of esculetin against oxidative stress are associated with the upregulation of Nrf2-mediated NQO1 expression via the activation of the ERK pathway

Abstract: Esculetin, a coumarin derivative isolated from a variety of medicinal herbs, has been reported to possess multiple therapeutic and pharmacological actions. Although several studies have demonstrated the antioxidant activity of esculetin, its mechanisms of action have not been clearly established. The aim of this study was to evaluate the effects of esculetin against hydrogen peroxide (H2O2)‑induced oxidative stress in C2C12 myoblasts and to investigate the mechanisms involved in this process. Our data indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
8
22
0
Order By: Relevance
“…36 As a detoxifiying enzyme, NQO1 catalyzes the 2-electron reductive metabolism and detoxification of quinies, protecting cells from oxidative stress-induced injury. 37 Indeed, in the current study, the Nrf2 nuclear translocation was found to be inhibited in AGEs-exposed aorta. After treatment of matrine-type alkaloids, the nuclear translocation of Nrf2 increased dramatically.…”
Section: Discussionsupporting
confidence: 47%
“…36 As a detoxifiying enzyme, NQO1 catalyzes the 2-electron reductive metabolism and detoxification of quinies, protecting cells from oxidative stress-induced injury. 37 Indeed, in the current study, the Nrf2 nuclear translocation was found to be inhibited in AGEs-exposed aorta. After treatment of matrine-type alkaloids, the nuclear translocation of Nrf2 increased dramatically.…”
Section: Discussionsupporting
confidence: 47%
“…Sen et al demonstrated the role of esculetin in attenuating the progression of diabetic nephropathy via Nrf2 activation and inhibition of HGinduced ROS production [166]. Han et al reported that esculetin protected against H 2 O 2 -induced ROS accumulation in the myoblasts through the activation of the Nrf2/NQO1 pathway [167]. Treatment of the pancreatic cancer cell lines with esculetin resulted in significant inhibition of cell proliferation, intracellular ROS, and protein levels of NF-κB [168].…”
Section: Urolithin Amentioning
confidence: 99%
“…3 ). Furthermore, NDRG2 alleviation of photoreceptor oxidative stress resulted in restriction of the stimulated photoreceptor antioxidant defense responses under damaging conditions, as shown by inhibited mRNA expression levels of the antioxidant master transcription factor Nuclear factor E2-related factor 2 (Nrf2) 31 and the regulated antioxidant genes Heme oxygenase-1 (Ho-1) 32 and NAD(P)H:quinone oxidoreductase-1 (Nqo-1) 33 (Fig. 5k, l ).…”
Section: Resultsmentioning
confidence: 97%